Pooling data for primary total knee implants across national registries: is the same implant used in multiple registries and for the same patient group? An observational study - Lotje Hoogervorst; Rob G H H Nelissen; Liza van Steenbergen; Alma B Pedersen; Eskild Bendix Kristiansen; Martin Lindberg-Larsen; Marina Torre; Enrico Ciminello; Riccardo Valentini; Alexander W Grimberg; Yinan Wu; Perla J Marang-van de Mheen (Acta Orthopaedica)
Background and purpose: Pooling data on the performance of total knee (TK) implants across registries is only possible if the same TK implant is used across multiple registries and if used in patients with similar characteristics. We assessed to what extent specific TK implants: (i) are used across multiple registries or only in a single registry; and (ii) differ in patient characteristics between registries. Methods: All primary TK implants implanted between January 2020 and December 2021 in the Danish, Dutch, German, and Italian registries were included. We determined the number of registries using a specific TK implant (based on combined femoral-tibial component brand name and fixation/congruency/mobile bearing insert/patella usage). Patient characteristics (age/body mass index [BMI]/sex/diagnosis osteoarthritis) were compared across registries for TK implants used in ≥ 2 registries ≥ 100 times. Results: 813 different TK implants (577,351 procedures) were used across the 4 registries, of which 53 TK implants (7%) were used in 1 registry (8,000 procedures). 760 different TK implants (569,351 procedures; 99%) were used in ≥ 2 registries of which 47 different TK implants (393,954 procedures; 68%) were used in ≥ 2 registries and ≥ 100 times. Statistically and clinically significant differences in age for the same TK implant across registries were observed for 29 TK implants (62%) and 3 TK implants (6%), respectively; for other characteristics these were for BMI 30 (64%) and 0 (0%) TK implants; for male proportion 23 (49%) and 17 (36%) TK implants; and for diagnosis of osteoarthritis 42 (89%) and 34 (72%) TK implants, respectively. Conclusion: Most specific TK implants and TK procedures were used across multiple registries, but they were often used in patients with different characteristics. This has an impact on comparing implant performances between registries.